A high-safety, long-cycle sodium-ion battery
By controlling the capacity release ratio of the negative electrode material in the sodium ion battery, adding specific fluoroether solvents and controlling the compaction density of the negative electrode, the problems of poor circulation performance and insufficient magnification performance of the sodium ion battery are solved, and high safety and long cycle life are achieved battery performance.
Patent Information
- Application Number
- CN202211510692.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-11-29
AI Technical Summary
Existing sodium ion batteries have problems with poor circulation performance and insufficient rate performance, especially sodium analysis.
By controlling the ratio of the platform area capacity to the slope area capacity of the negative electrode material is within the range of 0.66≤A/B≤2.34, combined with the addition of a specific fluoroether solvent to the electrolyte, the compaction density of the negative electrode is controlled to be between 0.85-1.00g/cm3 Within range.
It effectively inhibits the occurrence of sodium analysis, improves the cycle performance and rate performance of the battery, and ensures the high safety and long cycle life of the battery.
Smart Images

Figure CN118117147B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy storage, and in particular relates to a high-safety, long-cycle sodium ion battery. Background Art
[0002] In new energy storage technology, lithium-ion batteries have been widely used. Sodium-ion batteries have similar principles and structures to lithium-ion batteries, but compared with lithium batteries, sodium-ion batteries have wide resources, low costs, small fluctuations, a wider temperature range and higher safety performance. These characteristics have become favorable factors for sodium-ion batteries to replace lithium-ion batteries. With the continuous advancement of sodium-ion battery technology, sodium-ion batteries will occupy an important position in my country's energy system, especially in the field of energy storage, and have broad growth space. The development of high-performance, low-cost sodium-ion batteries is the decisive factor in determining whether they can be industrialized.
[0003] Current sodium-ion batteries are prone to sodium precipitation, and also have problems such as insufficient cycle performance and poor rate discharge capability. Therefore, it is necessary to research and improve sodium-ion batteries. Summary of the invention
[0004] The present invention is based on the inventor's discovery and understanding of the following facts and problems: Currently, sodium ion batteries generally have problems of poor cycle performance and insufficient rate performance. Therefore, it is necessary to conduct in-depth research on sodium ion batteries to inhibit the occurrence of sodium precipitation in order to improve the cycle performance and rate performance of sodium ion batteries.
[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a high-safety long-cycle sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein:
[0006] The slope region capacity A and the platform region capacity B corresponding to the discharge capacity curve of the negative electrode subjected to the power-off test satisfy the relationship: 0.66≤A / B≤2.34, wherein the slope region capacity A is the capacity release ratio in the power-off test voltage range of 0.1-3.0V, the platform region capacity B is the capacity release ratio in the power-off test voltage range of 0.1-0V, and A+B=1;
[0007] The electrolyte includes a fluoroether solvent, and the molecular formula of the fluoroether solvent is: x C n H 2n+1-x OC m H 2m+1 , wherein x / (2n+1)<80%, n / m>1.5, 4≤n≤10, 1≤m≤5, and the mass percentage C% of the fluoroether in the electrolyte is 7%≤C%≤30%;
[0008] The compaction density D of the negative electrode is 0.85-1.00 g / cm 3 .
[0009] Optionally, the mass content C% of the fluoroether in the electrolyte and the compaction density D of the negative electrode satisfy: 7<C / D<35.
[0010] Optionally, the mass content C% of the fluoroether in the electrolyte and the compaction density D of the negative electrode satisfy: 10≤C / D≤31.
[0011] Optional, 0.81≤A / B≤1.63.
[0012] Optionally, the fluoroether solvent is selected from at least one of 2,2,3,3,4,4,5,5-octafluoropentyl methyl ether, 2,2,3,3,4,4,5,5-octafluoropentyl ethyl ether, 2,2,3,3,4,4,5-heptafluoropentyl methyl ether, 2,2,3,4,4,5,5-heptafluoropentyl ethyl ether, 3,3,4,4,5,5-hexafluoropentyl methyl ether, 3,3,4,4,5,5-hexafluoropentyl ethyl ether, 2,2,3,3,4,4-hexafluorobutyl methyl ether, 2,2,3,3,4,4-hexafluoropentyl methyl ether or 2,2,3,3,4,4-hexafluorobutyl ethyl ether;
[0013] Preferably, the fluoroether solvent comprises one or more of 2,2,3,3,4,4,5,5-octafluoropentyl ethyl ether, 2,2,3,3,4,4,5,5-octafluoropentyl methyl ether, and 2,3,3,4,4,5,5-heptafluoropentyl methyl ether.
[0014] Optionally, the electrolyte further includes an auxiliary solvent, and the auxiliary solvent includes at least one of C3-C5 carbonates, C2-C6 carboxylates, and C4-C10 ethers, wherein:
[0015] The C3-C5 carbonate includes a cyclic carbonate or a chain carbonate having 3-5 carbon atoms. Preferably, the cyclic carbonate includes at least one of ethylene carbonate, vinylene carbonate, vinylethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonate includes at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate;
[0016] The C2-C6 carboxylic acid ester includes at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate and propyl propionate.
[0017] The ethers of C4-C10 include cyclic ethers or chain ethers with 4-10 carbon atoms; preferably, the cyclic ethers include at least one of 1,3-dioxolane, 1,4-dioxane, tetrahydrofuran, 2-methyltetrahydrofuran, 2-trifluoromethyltetrahydrofuran; the chain ethers include at least one of dimethoxymethane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether;
[0018] Optionally, the electrolyte includes an electrolyte salt, and the electrolyte salt includes at least one of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium trifluoroacetate (CF3COONa), sodium tetraphenylborate (NaB(C6H5)4), sodium trifluoromethanesulfonate (NaSO3CF3), sodium bis(fluorosulfonyl)imide (Na[(FSO2)2N]) or sodium bis(trifluoromethylsulfonyl)imide (Na[(CF3SO2)2N]).
[0019] Optionally, the electrolyte further includes an additive, and the additive includes a fluorinated carbonate. Preferably, the fluorinated carbonate includes at least one of fluoroethylene carbonate (FEC) or difluoroethylene carbonate (DFEC), and the mass percentage content of the fluorinated carbonate in the electrolyte is 1-5%.
[0020] Optionally, the positive electrode includes a positive electrode active material, and the positive electrode active material is selected from at least one of layered metal oxides, polyanion compounds, Prussian compounds, phosphate compounds, sulfate compounds, wherein,
[0021] The chemical formula of the layered metal oxide is Na x M y O z , 0 < x ≤ 1, 0 < y ≤ 1, 1 < z ≤ 2, and M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V; preferably, the layered metal oxide is NaNi m Fe n Mn p O2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1) or NaNi m Co n Mn p O2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1) or at least one of them;
[0022] The chemical formula of the Prussian compound is Na x M[M′(CN)6] y ·zH2O, M and M′ are transition metals, 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 20; preferably, the Prussian compound is Nax Mn[Fe(CN)6] y ·zH2O (0<x≤2, 0<y≤1, 0<z≤20) or Na x Fe[Fe(CN)6] y At least one of zH2O (0<x≤2, 0<y≤1, 0<z≤20);
[0023] The chemical formula of the phosphate compound is Na3(MO 1-x PO4)2F 1+2x , 0≤x≤1, M is selected from at least one of Al, V, Ge, Fe, and Ga, preferably, the phosphate compound is at least one of Na3(VPO4)2F3 or Na3(VOPO4)2F; or, the chemical formula of the phosphate compound is Na2MPO4F, M is selected from at least one of Fe and Mn, preferably, the phosphate compound is at least one of Na2FePO4F or Na2MnPO4F;
[0024] The chemical formula of the sulfate compound is Na2M(SO4)2·2H2O, where M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V;
[0025] Optionally, the negative electrode includes a negative electrode active material and a conductive agent, the negative electrode active material includes at least one of hard carbon or soft carbon; the particle size of the negative electrode active material satisfies 4 μm ≤ d 50 ≤8μm; in the negative electrode, the mass percentage of the conductive agent is 1% to 5%.
[0026] According to the high-safety long-cycle sodium-ion battery provided by the present invention, the inventors found in their research that by controlling the platform area capacity and slope area capacity ratio of the negative electrode material used in the battery to meet 0.66≤A / B≤2.34, it is possible to ensure that the capacity of the negative electrode is fully utilized, stabilize the positive and negative electrode capacity release ratio, and make the Na2O3 released from the positive electrode + Can be fully embedded in the negative electrode to prevent Na + It precipitates at the negative electrode, effectively suppressing the occurrence of sodium precipitation, and improving the cycle performance and rate performance of the battery. At the same time, the present invention uses fluoroether as a co-solvent in the electrolyte. The fluoroether solvent can participate in the solvation structure of the ions, affecting the composition of the interface film SEI and CEI, improving the film quality, and improving the interface stability between the electrode material and the electrolyte, thereby improving the cycle performance of the battery. However, the inventors also found in the study that the addition of the fluoroether solvent of the present invention will cause the wettability of the electrolyte to decrease. Based on this, the inventors further found that the compaction density of the negative electrode is controlled to 0.85-1.00g / cm 3, which can improve the wetting effect of the negative electrode, and make the negative electrode have excellent wettability while ensuring that the battery has sufficient energy density, shorten the wetting time of battery production, and is conducive to improving the film-forming effect during the battery activation process. The present invention effectively improves the performance of sodium-ion batteries by controlling the ratio of the platform area capacity to the slope area capacity of the negative electrode, adding a specific fluoroether solvent to the electrolyte, and controlling the compaction density of the negative electrode, especially greatly improving the rate performance and cycle performance, and no sodium precipitation occurs. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the voltage-capacity curve of the negative electrode in the sodium ion battery of the present invention in the buckle test.
[0028] Figure 2 This is a sodium precipitation test photo of the sodium ion battery prepared in Example 1.
[0029] Figure 3 This is a sodium precipitation test photo of the sodium ion battery prepared in Example 1. DETAILED DESCRIPTION
[0030] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0031] A high-safety, long-cycle sodium-ion battery according to an embodiment of the present invention comprises a positive electrode, a negative electrode and an electrolyte, wherein:
[0032] The slope area capacity A and the platform area capacity B corresponding to the discharge capacity curve of the negative electrode subjected to the power-off test satisfy the relationship: 0.66≤A / B≤2.34, wherein the slope area capacity A is the capacity release ratio in the power-off test voltage range of 0.1-3.0V, and the platform area capacity B is the capacity release ratio in the power-off test voltage range of 0.1-0V, A+B=1, the slope area capacity A satisfies 0.4≤A≤0.7, and the platform area capacity B satisfies 0.3≤B≤0.6;
[0033] The electrolyte includes a fluoroether solvent, and the molecular formula of the fluoroether solvent is: x C n H 2n+1-x OC m H 2m+1 , wherein x / (2n+1)<80%, n / m>1.5, 4≤n≤10, 1≤m≤5, and the mass percentage C% of the fluoroether in the electrolyte is 7%≤C%≤30%;
[0034] The compaction density D of the negative electrode is 0.85-1.00 g / cm 3 .
[0035] In a specific embodiment, the compaction density D of the negative electrode can be 0.85 g / cm 3 , 0.86g / cm 3 , 0.87g / cm 3 , 0.88g / cm 3 , 0.89g / cm 3 , 0.90g / cm 3 、0.91g / cm 3 、0.92g / cm 3 , 0.93g / cm 3 、0.94g / cm 3 , 0.95g / cm 3 , 0.96g / cm 3 , 0.97g / cm 3 、0.98g / cm 3 , 0.99g / cm 3 , 1.00g / cm 3 The compaction density of the negative electrode is greater than 1.00g / cm 3 , which will cause poor wettability of the negative electrode, affect the film formation effect, and deteriorate the cycle and rate performance; the negative electrode compaction density is less than 0.85g / cm 3 , which will reduce the overall energy density of the battery and affect the battery capacity.
[0036] In a specific embodiment, the mass content C% of the fluoroether in the electrolyte and the compaction density D of the negative electrode satisfy: 7<C / D<35.
[0037] In a specific embodiment, the C / D of the mass content C% of the fluoroether in the electrolyte and the compaction density D of the negative electrode can be: 7.5, 8, 9, 10, 12, 15, 18, 20, 22, 24, 26, 28, 30, 31, 33, or 35.
[0038] In a preferred embodiment, the mass content C% of the fluoroether in the electrolyte and the compaction density D of the negative electrode satisfy: 10≤C / D≤31.
[0039] In the present invention, by controlling the ratio of the fluoroether solvent content in the electrolyte to the compacted density of the negative electrode, the battery that meets the requirements of the present invention can ensure that the battery has sufficient wettability, solve the problem of poor battery wettability caused by the high viscosity of the fluoroether, ensure the battery capacity while improving the film formation stability of the electrolyte and the electrode material, and promote the cycle performance.
[0040] In a specific embodiment, the A / B values of the slope area capacity A and the platform area capacity B corresponding to the discharge capacity curve of the negative electrode for the power-on test can be 0.66, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, and 2.34.
[0041] Through extensive research, the inventors found that when A / B is less than 0.66, the capacity of the negative electrode material is released too low, resulting in sodium precipitation in the entire battery, deteriorating the battery's cycle performance, and increasing the battery's safety risk; when A / B is greater than 2.34, it will also cause the negative electrode material capacity to be released too low, resulting in sodium precipitation in the entire battery, deteriorating the battery's cycle performance, and increasing the battery's safety risk.
[0042] In a preferred embodiment, the slope region capacity A and the platform region capacity B corresponding to the discharge capacity curve of the negative electrode in the power-off test satisfy: 0.81≤A / B≤1.63.
[0043] In the present invention, the ratio of the capacity A in the slope region and the capacity B in the platform region corresponding to the discharge capacity curve of the negative electrode for the power-on test is further controlled to be 0.81-1.63, thereby further improving the cycle performance and rate performance of the sodium ion battery while ensuring no sodium precipitation.
[0044] In a specific embodiment, the fluoroether solvent is selected from one or more of 2,2,3,3,4,4,5,5-octafluoropentyl methyl ether, 2,2,3,3,4,4,5,5-octafluoropentyl ethyl ether, 2,3,3,4,4,5,5-heptafluoropentyl methyl ether, 2,3,3,4,4,5,5-heptafluoropentyl ethyl ether, 2,2,3,3,4,4,5-heptafluoropentyl methyl ether, 2,2,3,4,4,5,5-heptafluoropentyl ethyl ether, 3,3,4,4,5,5-hexafluoropentyl methyl ether, 3,3,4,4,5,5-hexafluoropentyl ethyl ether, 2,2,3,3,4,4-hexafluorobutyl methyl ether, 2,2,3,3,4,4-hexafluoropentyl methyl ether and 2,2,3,3,4,4-hexafluorobutyl ethyl ether.
[0045] In a preferred embodiment, the fluoroether solvent includes one or more of 2,2,3,3,4,4,5,5-octafluoropentyl ethyl ether, 2,2,3,3,4,4,5,5-octafluoropentyl methyl ether, and 2,3,3,4,4,5,5-heptafluoropentyl methyl ether.
[0046] Furthermore, the specific structure of the above fluoroether compound can be shown in the following table:
[0047]
[0048] In a specific embodiment, the mass percentage of the fluoroether solvent in the electrolyte can be 7%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, or 30%.
[0049] Fluoroether solvents are added to the electrolyte, which can partially replace the solvents of conventional electrolytes such as EMC, form co-solvents with other solvents, participate in the solvation structure of ions, affect the formation of SEI and CEI, and improve the interface stability between electrode materials and electrolytes. The present invention controls the mass content of fluoroether solvents in the electrolyte to be 7-30%. If the content of fluoroether solvents is too low, the conductivity of the electrolyte will be too low; if the content of fluoroether solvents is too high, it will make it difficult to dissolve electrolyte salts.
[0050] In a specific embodiment, the electrolyte further includes an auxiliary solvent, and the auxiliary solvent includes at least one of C3-C5 carbonates, C2-C6 carboxylates, and C4-C10 ethers.
[0051] In a preferred embodiment, the C3-C5 carbonate includes a cyclic carbonate or a chain carbonate having 3 to 5 carbon atoms. Further preferably, the cyclic carbonate includes at least one of ethylene carbonate, vinylene carbonate, vinylethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonate includes at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate.
[0052] In a preferred embodiment, the C2-C6 carboxylic acid ester includes at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and propyl propionate.
[0053] In a preferred embodiment, the C4-C10 ether includes a cyclic ether or a chain ether having 4 to 10 carbon atoms; further preferably, the cyclic ether includes at least one of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ether includes at least one of dimethoxymethane, 1,2-dimethoxyethane, and diethylene glycol dimethyl ether.
[0054] In the embodiments of the present invention, there is no particular limitation on solvents other than the fluoroether compound, and any solvent commonly used in sodium ion batteries can be applied to the present invention.
[0055] In a specific embodiment, the electrolyte includes an electrolyte salt, and the electrolyte salt includes at least one of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium trifluoroacetate (CF3COONa), sodium tetraphenylborate (NaB(C6H5)4), sodium trifluoromethanesulfonate (NaSO3CF3), sodium bis(fluorosulfonyl)imide (Na[(FSO2)2N]), or sodium bis(trifluoromethylsulfonyl)imide (Na[(CF3SO2)2N]).
[0056] In the embodiments of the present invention, there is no particular limitation on the electrolyte salt, and the electrolyte salts commonly used in sodium-ion batteries can all be applicable to the present invention.
[0057] In a specific embodiment, the electrolyte further includes an additive, and the additive includes a fluorinated carbonate. Preferably, the fluorinated carbonate includes at least one of fluoroethylene carbonate (FEC) or difluoroethylene carbonate (DFEC); the mass percentage content of the fluorinated carbonate in the electrolyte is 1-5%. In the embodiments of the present invention, the electrolyte can further include the additive fluorinated carbonate, which can further improve the film-forming quality and is beneficial to improving the battery performance.
[0058] In a specific embodiment, the positive electrode includes a positive electrode active material, and the positive electrode active material is selected from at least one of layered metal oxides, polyanion compounds, Prussian compounds, phosphate compounds, and sulfate compounds.
[0059] In a preferred embodiment, the chemical formula of the layered metal oxide is Na x M y O z , 0 < x ≤ 1, 0 < y ≤ 1, 1 < z ≤ 2, and M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V; more preferably, the layered metal oxide is NaNi m Fe n Mn p O2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1) or NaNi m Co n Mn p O2 (m + n + p = 1, 0 ≤ m ≤ 1, 0 ≤ n ≤ 1, 0 ≤ p ≤ 1) or at least one of them.
[0060] In a preferred embodiment, the chemical formula of the Prussian compound is Na x M[M′(CN)6] y ·zH2O, M and M′ are transition metals, 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 20; more preferably, the Prussian compound is Nax Mn[Fe(CN)6] y ·zH2O (0<x≤2, 0<y≤1, 0<z≤20) or Na x Fe[Fe(CN)6] y At least one of zH2O (0<x≤2, 0<y≤1, 0<z≤20).
[0061] In a preferred embodiment, the chemical formula of the phosphate compound is Na3(MO 1-x PO4)2F 1+2x , 0≤x≤1, M is selected from at least one of Al, V, Ge, Fe, and Ga, and more preferably, the phosphate compound is at least one of Na3(VPO4)2F3 or Na3(VOPO4)2F; or, the chemical formula of the phosphate compound is Na2MPO4F, M is selected from at least one of Fe and Mn, and more preferably, the phosphate compound is at least one of Na2FePO4F or Na2MnPO4F;
[0062] In a preferred embodiment, the chemical formula of the sulfate compound is Na2M(SO4)2·2H2O, where M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V.
[0063] In the embodiment of the present invention, the positive electrode active material in the positive electrode is preferably selected, which can cooperate with the additive used in the present invention to form a film, improve the film formation quality, and is conducive to further improving the performance of the battery.
[0064] In a specific embodiment, the negative electrode includes a negative electrode active material and a conductive agent, wherein the negative electrode active material includes at least one of hard carbon or soft carbon; and the particle size of the negative electrode active material satisfies 4 μm ≤ d 50 ≤8μm; in the negative electrode, the mass percentage of the conductive agent is 1% to 5%.
[0065] In a specific embodiment, the particle size of the negative electrode active material may be 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, or 8 μm.
[0066] In a specific embodiment, the mass percentage of the conductive agent in the negative electrode can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%.
[0067] In the present invention, the slope area capacity A and the platform area capacity B are obtained by performing a button half-cell test on the negative electrode. The specific steps are as follows:
[0068] (1) Using the LAND test system, the negative electrode was tested. First, it was discharged to 0 V at a current density of 0.1 C, and the voltage range was set to 0-1.5 V, and the discharge capacity was 1. After standing for 10 min, it was charged to 1.5 V at a current density of 0.1 C, and the charge capacity was 2.
[0069] (2) According to the procedure of step (1), the discharge and charge curves of the negative electrode can be obtained. During discharge, the voltage-capacity curve when discharged to 0 V is the platform region and slope region curve in the present invention, see Figure 1 .
[0070] In the present invention, the slope zone capacity A and the platform zone capacity B corresponding to the discharge capacity curve of the negative electrode subjected to the power-off test using the above method satisfy the relationship: 0.66≤A / B≤2.34, wherein the slope zone capacity A is the capacity release ratio in the power-off test voltage range of 0.1-3.0V, the platform zone capacity B is the capacity release ratio in the power-off test voltage range of 0.1-0V, and A+B=1.
[0071] In the present invention, the regulation method of the slope zone capacity and the platform zone capacity in the negative electrode withholding test is: by controlling the particle size of the negative electrode active material particles in the negative electrode of the sodium ion battery of the present invention, the amount of the conductive agent in the negative electrode, and the amount of the negative electrode film-forming additive in the electrolyte, the ratio (A / B) of the slope zone capacity A and the platform zone capacity B can be controlled.
[0072] Among them, when the particle size of the negative electrode active material satisfies 4μm≤d 50 ≤8μm, when the mass content of the conductive agent in the negative electrode plate is 1% to 5%, and the mass content of the negative electrode film-forming additive in the electrolyte is 1% to 5%, it is possible to achieve the regulation of the slope zone capacity A and the platform zone capacity B to satisfy the relationship: 0.66≤A / B≤2.34.
[0073] The inventors found in the course of the experiment that the relationship between the particle size of the negative electrode active material, the amount of the negative electrode conductive agent, and the amount of the negative electrode film-forming additive in the electrolyte and the ratio of the capacity A in the slope area to the capacity B in the platform area (A / B) is as follows: as the particle size of the negative electrode active material and the amount of the negative electrode film-forming additive increase, the surface defects and pores of the negative electrode increase, and the ratio of A / B increases; as the amount of the negative electrode conductive agent increases, sodium ions are more easily embedded in the negative electrode, and the ratio of A / B decreases. 50 The relationship between the amount of conductive agent in the negative electrode and the amount of negative electrode film-forming additive in the electrolyte and A / B can be summarized in Table 1.
[0074] Table 1
[0075] Influencing factors Numerical range Impact on A / B <![CDATA[Negative electrode active material particle size d 50 > <![CDATA[4μm≤d 50 ≤8μm]]> The particle size of the negative electrode active material increases, and the A / B ratio increases Conductive agent dosage in negative electrode 1%~5% The amount of negative electrode conductive agent increases, and the A / B ratio decreases Amount of negative electrode film-forming additive in electrolyte 1%~5% The amount of film-forming additives increases, and the A / B ratio increases
[0076] For example, by controlling the particle size d of the negative electrode active material 50 Examples of adjusting the A / B ratio by adjusting the amount of negative electrode conductive agent and the amount of negative electrode film-forming additive in the electrolyte can be seen in Table 2.
[0077] Table 2
[0078]
[0079]
[0080] The present invention is described in detail below with reference to the embodiments and the accompanying drawings.
[0081] The fluoroether solvent in the embodiment of the present invention can be prepared by the preparation method of fluoroether disclosed in the prior art.
[0082] Example 1
[0083] (1) Preparation of fluoroethers: The synthesis method of the fluoroethers of the present invention can be to use the corresponding alcohol to react with an alcohol reagent or other alkylating reagent in NMP solvent under the catalysis of NaOH to produce the corresponding ether.
[0084] Taking Example 1 as an example, 2,2,3,3,4,4,5,5-octafluoro-1-pentanol was reacted with ethanol in NMP solvent under the catalysis of NaOH to obtain 2,2,3,3,4,4,5,5-octafluoropentyl ethyl ether.
[0085] (2) Preparation of electrolyte: 9 wt % of electrolyte salt NaPF6, 14 wt % of fluoroether solvent 2,2,3,3,4,4,5,5-octafluoropentyl ethyl ether, 76 wt % of auxiliary solvent (a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC), and ethyl methyl carbonate (EMC) in a mass ratio of 20:10:70), and 1 wt % of negative electrode film-forming additive fluoroethylene carbonate FEC were mixed uniformly to obtain an electrolyte.
[0086] (3) Preparation of positive electrode: binder polyvinylidene fluoride, solvent N-methylpyrrolidone, conductive agent acetylene black, positive electrode active material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is mixed evenly to obtain positive electrode slurry, the positive electrode slurry is coated on the current collector, and the positive electrode sheet is obtained through coating, drying and rolling processes.
[0087] (4) Preparation of negative electrode: The negative electrode active material hard carbon (d 504.5μm), conductive agent carbon black, solvent water, and binder sodium carboxymethyl cellulose are mixed evenly to obtain negative electrode slurry, which is coated on the current collector. After coating, drying, and rolling, the negative electrode sheet is obtained. The mass content of the conductive agent in the negative electrode is 5%. The compacted density of the negative electrode is 1.0g / cm 3 .
[0088] (5) Battery assembly
[0089] A PP separator is placed between the positive electrode sheet and the negative electrode sheet prepared above, and then the sandwich structure consisting of the positive electrode sheet, the negative electrode sheet and the separator is wound, and then the wound body is flattened and placed in an aluminum foil packaging bag, and vacuum baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid; the electrolyte prepared above is injected into the battery cell through the injection hole, and the amount of electrolyte must be guaranteed to fill the gaps in the battery cell, and the sodium ion battery is encapsulated.
[0090] After the charge-off test, the ratio of the capacity in the slope region to the capacity in the platform region of the negative electrode in this embodiment is A / B=0.66.
[0091] Embodiments 2 to 26
[0092] Examples 2 to 26 are used to illustrate the sodium ion battery disclosed in the present invention, and include most of the operating steps in Example 1, except that:
[0093] The fluoroether solvents and their contents used in Examples 2 to 26, the ratio A / B of the capacity in the slope area to the capacity in the platform area of the negative electrode after the withholding test, the ratio C / D of the mass content C% of the fluoroether and the compaction density D of the negative electrode are shown in Table 3.
[0094] Comparative Examples 1 to 9
[0095] Comparative Examples 1 to 9 are used to compare and illustrate the sodium ion battery disclosed in the present invention, including most of the operating steps in Example 1, except that:
[0096] The fluoroether solvents and their contents used in Comparative Examples 1 to 9, the ratio A / B of the capacity in the slope area to the capacity in the platform area of the negative electrode after the withholding test, the ratio C / D of the mass content C% of the fluoroether and the compaction density D of the negative electrode are shown in Table 4.
[0097] Table 3
[0098]
[0099] Table 4
[0100]
[0101] Performance Testing
[0102] The sodium ion battery prepared above was subjected to the first efficiency and cycle charge and discharge tests in the voltage range of 1.5 to 3.95 V, and the charge and discharge capacity of the first formation and capacity distribution of the battery and the capacity retention rate after 200 cycles were recorded. The details are as follows:
[0103] (1) 4C rate discharge capacity ratio
[0104] The capacity C2 released by the sodium ion battery when discharged from 3.95V to 1.5V at a rate of 4C and the capacity C1 released by the battery when discharged from 3.95V to 1.5V at a rate of 0.2C during the initial activation stage are measured. The calculation formula is as follows:
[0105] 4C rate discharge capacity ratio = C2 / C1.
[0106] (2) Normal temperature cycle performance test
[0107] The sodium ion battery was placed in a constant temperature environment of 25°C, charged at a constant current of 0.5C to 3.95V, then charged at a constant voltage until the current dropped to 0.03C, and then discharged at a constant current of 1C to 1.5V. This cycle was repeated, and the discharge capacity of the first cycle and the discharge capacity of the last cycle were recorded.
[0108] The capacity retention rate of 25℃ cycle is calculated as follows:
[0109] Capacity retention rate (%) = discharge capacity of the last cycle / discharge capacity of the first cycle×100%.
[0110] (3) High temperature cycle capacity retention rate
[0111] The sodium ion battery was placed in a constant temperature environment of 45°C, charged at a constant current of 0.5C to 3.95V, then charged at a constant voltage until the current dropped to 0.03C, and then discharged at a constant current of 1C to 1.5V. This cycle was repeated for 200 times, and the discharge capacity and battery volume of the first cycle, as well as the discharge capacity and battery volume of the 200th cycle were recorded.
[0112] The capacity retention rate of 45℃ cycle is calculated as follows:
[0113] Capacity retention rate (%) = discharge capacity at the last cycle / discharge capacity at the 200th cycle×100%.
[0114] (4) Battery sodium precipitation test
[0115] The sodium ion battery was charged at a constant current of 1C and a constant voltage of 3.95V, and then charged at 0.03C and discharged at 1C / 1.5V. Afterwards, the battery was disassembled after 50 cycles to evaluate the effect of the sodium ion battery on inhibiting sodium precipitation at the negative electrode.
[0116] The performance data of the batteries prepared in Examples 1 to 26 and Comparative Examples 1 to 9 are shown in Tables 5 to 8, and the sodium precipitation test results of Example 1 are shown in Tables 5 to 8. Figure 2 The sodium analysis test results of Comparative Example 1 are shown in Figure 3 .
[0117] Table 5
[0118]
[0119] It can be seen from Table 5 that for the batteries prepared in Examples 1-7 of the present invention, the discharge capacity curves of the negative electrodes for the charge-off test correspond to the slope capacity A and the platform capacity B, which satisfy the relationship: 0.66≤A / B≤2.34, which enables the capacity of the negative electrode to be fully utilized, and the Na2O3 released from the positive electrode can be fully utilized. + Can be fully embedded in the negative electrode, effectively preventing Na + In the case of negative electrode precipitation, no sodium precipitation occurs in Examples 1-7, and the embodiments have excellent cycle performance and rate performance. The 4C rate discharge capacity ratio can reach more than 87%, the capacity retention rate after 200 cycles at room temperature can reach more than 92%, and the capacity retention rate after 200 cycles at high temperature can reach more than 90.5%.
[0120] In Comparative Example 1, the ratio A / B of the capacity A in the slope area and the capacity B in the platform area of the negative electrode in the buckle test is too large, resulting in too low release of the capacity of the negative electrode material, leading to sodium precipitation in the whole battery, such as Figure 3 As shown, the cycle performance of the battery is deteriorated, the safety risk of the battery is increased, and the capacity retention rate of 200 cycles of high temperature cycle is only 83.2%. At the same time, the rate performance is seriously reduced, and the 4C rate discharge capacity ratio is reduced to 65.0%. In comparative example 2, the ratio A / B of the capacity A in the slope area of the negative electrode in the buckle test to the capacity B in the platform area is too small, which also causes the negative electrode material capacity to be released too low, resulting in sodium precipitation, and deteriorating the cycle performance and rate performance of the battery. The 4C rate discharge capacity ratio is reduced to 68.0%, and the capacity retention rate of 200 cycles of high temperature cycle is reduced to 81.90.
[0121] Table 6
[0122]
[0123] It can be seen from Table 6 that in Examples 8-17, the content of fluoroether in the electrolyte is controlled at 7-30%, and the compaction density of the negative electrode is controlled at 0.85-1.00 g / cm 3 The batteries produced have excellent rate performance and cycle performance. The 4C rate discharge capacity ratio can reach more than 85%, the capacity retention rate after 200 cycles at room temperature can reach more than 92.5%, and the capacity retention rate after 200 cycles at high temperature can reach more than 91%.
[0124] In Comparative Example 3, the compaction density of the negative electrode in the sodium ion battery is relatively low, only 0.75 g / cm 3 The addition of fluoroether will lead to poor wettability, and the use of a negative electrode with a lower compaction density cannot compensate for the decrease in wettability caused by fluoroether, and cannot effectively improve the wettability, which is not conducive to improving the performance of sodium-ion batteries. The capacity retention rate after 200 cycles of high-temperature cycling drops to 81.6%.
[0125] In Comparative Example 4, the compaction density of the negative electrode in the sodium ion battery is relatively high, reaching 1.2 g / cm 3 , which will cause poor wettability of the negative electrode and affect the film-forming effect, thereby deteriorating the performance of the battery. The capacity retention rate of the battery prepared in Comparative Example 4 dropped to 76.5% after 200 cycles at room temperature, and dropped to 74.3% after 200 cycles at high temperature.
[0126] In Comparative Example 5, no fluoroether solvent is added to the electrolyte, and the stability of the CEI and SEI films formed on the positive and negative electrode sides is poor. During the cycle, the electrolyte continues to undergo side reactions, resulting in continuous consumption of the electrolyte and active substances, causing battery performance to deteriorate. The conductivity drops to 5.25 mS / cm, the 4C rate discharge capacity ratio drops to 79.8%, the capacity retention rate after 200 cycles at room temperature drops to 80.4%, and the capacity retention rate after 200 cycles at high temperature drops to 79.2%.
[0127] In Comparative Example 6, too little fluoroether solvent was added to the electrolyte, and the fluoroether could not effectively participate in the film formation and could not effectively regulate the interface film. The battery performance was not significantly improved, the conductivity was only 5.89 mS / cm, and the capacity retention rate after 200 cycles at room temperature was only 84.9%, and the capacity retention rate after 200 cycles at high temperature was only 82.6%.
[0128] In Comparative Example 7, too much fluoroether solvent was added to the electrolyte, causing the fluoroether to excessively participate in the formation of CEI and SEI films, making the interface film too thick and uneven, and deteriorating the cycle performance of the battery. The capacity retention rate after 200 cycles at room temperature can only reach 84.3%, and the capacity retention rate after 200 cycles at high temperature can only reach 83.1%.
[0129] Table 7
[0130]
[0131] It can be seen from Table 7 that the fluoroether solvent structures used in Examples 1, 18-21 all satisfy F x C n H 2n+1- x OC m H 2m+1, where x / (2n+1)<80%, n / m>1.5, 4≤n≤10, 1≤m≤5 are met. The prepared batteries have good rate performance and cycle performance, achieving a balance between battery rate performance and cycle performance. The 4C rate discharge capacity ratio can reach more than 84%, the capacity retention rate after 200 cycles at room temperature can reach more than 92%, and the capacity retention rate after 200 cycles at high temperature can reach more than 91%.
[0132] In Comparative Example 8, the fluoroether solvent added to the electrolyte is 2,2,3,3,3-pentafluoropropyl methyl ether, and the n value is only 3, which does not meet the requirements of the present invention for fluoroether solvents. The ionic conductivity, rate performance and cycle performance of the prepared battery are greatly reduced. The electrolyte conductivity at 25°C is only 5.29 mS / cm, the 4C rate discharge capacity ratio is reduced to 78.9%, the capacity retention rate after 200 cycles at room temperature is reduced to 77.9%, and the capacity retention rate after 200 cycles at high temperature is reduced to 76.8%.
[0133] In Comparative Example 9, the fluoroether solvent added to the electrolyte is 1,1,2,2,3,3,4,4,5-nonafluorobutyl methyl ether. Although n and m both meet the requirements of the present invention for the fluoroether solvent, there are too many F atoms, x / (2n+1)=100%, which is greater than 80%, and does not meet the requirements of the present invention for the fluoroether solvent. The ionic conductivity, rate performance and cycle performance of the battery prepared in Comparative Example 9 are greatly reduced. The electrolyte conductivity at 25°C is only 5.46 mS / cm, the 4C rate discharge capacity ratio is reduced to 79.8%, the capacity retention rate after 200 cycles at room temperature is reduced to 76.9%, and the capacity retention rate after 200 cycles at high temperature is reduced to 75.3%.
[0134] Table 8
[0135]
[0136] It can be seen from Table 8 that in Examples 22-26, different types of negative electrode materials, conductive agents, and negative electrode film-forming additives were used, and the batteries prepared had good rate performance and cycle performance, and there was no sodium precipitation phenomenon. The 4C rate discharge capacity ratio could all reach more than 82%, the capacity retention rate after 200 cycles at room temperature could reach more than 91.5%, and the capacity retention rate after 200 cycles at high temperature could reach more than 90%, indicating that different types of negative electrode materials, conductive agents, and negative electrode film-forming additives can be applied to the batteries of the embodiments of the present invention.
[0137] In summary, it can be seen from Tables 5-8 that the sodium ion battery prepared in Example 1-26 provides sufficient negative electrode capacity release by controlling the ratio A / B of the slope area capacity and the platform area capacity corresponding to the discharge capacity curve of the negative electrode in the sodium ion battery in the buckle test within the range of 0.66-2.34, effectively suppressing the sodium precipitation phenomenon, while improving the cycle performance and rate performance of the battery, and improving the safety performance of the battery. In the embodiment of the present invention, a specific fluoroether solvent is used as a co-solvent in the electrolyte, which can improve the conductivity and electrochemical and thermal stability of the electrolyte. The fluoroether solvent can participate in the formation of CEI and SEI films, reduce the occurrence of side reactions, improve the film quality, and thus improve the interface stability. In addition, in the embodiment of the present invention, the compaction density of the negative electrode active material is controlled, which makes up for the decrease in wettability caused by the addition of the fluoroether solvent, improves the battery wettability, shortens the infiltration time of the battery, and at the same time, by controlling the compaction density of the negative electrode, the film quality can be improved during the battery activation process, which is conducive to suppressing the occurrence of the sodium precipitation phenomenon and improving the performance of the battery. The sodium ion battery of the embodiment of the present invention can have a capacity retention rate of up to 96.5% after 200 cycles of high-temperature cycling, a 4C rate discharge capacity ratio of up to 91%, and no sodium precipitation occurs, thus having excellent performance.
[0138] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0139] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A high-safety long-cycle sodium ion battery, characterized in that: It includes a positive electrode, a negative electrode and an electrolyte, wherein: The slope region capacity A and the platform region capacity B corresponding to the discharge capacity curve of the negative electrode subjected to the power-off test satisfy the relationship: 0.66≤A / B≤2.34, wherein the slope region capacity A is the capacity release ratio in the power-off test voltage range of 0.1-3.0V, the platform region capacity B is the capacity release ratio in the power-off test voltage range of 0.1-0V, and A+B=1; The electrolyte includes a fluoroether solvent, and the molecular formula of the fluoroether solvent is: x C n H 2n+1-x OC m H 2m+1 , wherein x / (2n+1)<80%, n / m>1.5, 4≤n≤10, 1≤m≤5, and the mass percentage content C% of the fluoroether in the electrolyte is 7%≤C%≤30%; The compaction density D of the negative electrode is 0.85-1.00 g / cm 3 .
2. The high-safety long-cycle sodium ion battery according to claim 1, characterized in that: The mass content C% of the fluoroether in the electrolyte and the compaction density D of the negative electrode satisfy: 7<C / D<35.
3. The high-safety long-cycle sodium ion battery according to claim 2, characterized in that: The mass content C% of the fluoroether in the electrolyte and the compaction density D of the negative electrode satisfy: 10≤C / D≤31.
4. The high-safety long-cycle sodium ion battery according to claim 1, characterized in that: 0.81≤A / B≤1.
63.
5. The high-safety long-cycle sodium ion battery according to claim 1, characterized in that: The fluoroether solvent is selected from one or more of 2,2,3,3,4,4,5,5-octafluoropentyl methyl ether, 2,2,3,3,4,4,5,5-octafluoropentyl ethyl ether, 2,3,3,4,4,5,5-heptafluoropentyl methyl ether, 2,3,3,4,4,5,5-heptafluoropentyl ethyl ether, 2,2,3,3,4,4,5-heptafluoropentyl methyl ether, 2,2,3,4,4,5,5-heptafluoropentyl ethyl ether, 3,3,4,4,5,5-hexafluoropentyl methyl ether, 3,3,4,4,5,5-hexafluoropentyl ethyl ether, 2,2,3,3,4,4-hexafluorobutyl methyl ether, 2,2,3,3,4,4-hexafluoropentyl methyl ether and 2,2,3,3,4,4-hexafluorobutyl ethyl ether.
6. The high-safety long-cycle sodium ion battery according to claim 5, characterized in that: The fluoroether solvent includes one or more of 2,2,3,3,4,4,5,5-octafluoropentyl ethyl ether, 2,2,3,3,4,4,5,5-octafluoropentyl methyl ether, and 2,3,3,4,4,5,5-heptafluoropentyl methyl ether.
7. The high-safety long-cycle sodium ion battery according to claim 1, characterized in that: The electrolyte also includes an auxiliary solvent, which includes at least one of C3-C5 carbonates, C2-C6 carboxylates, and C4-C10 ethers, wherein: The C3-C5 carbonates include cyclic carbonates or chain carbonates having 3-5 carbon atoms; The C2-C6 carboxylic acid ester includes at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and propyl propionate. The C4-C10 ethers include cyclic ethers or chain ethers having 4-10 carbon atoms.
8. The high-safety long-cycle sodium ion battery according to claim 7, characterized in that: The cyclic carbonate includes at least one of ethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonate includes at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate.
9. The high-safety long-cycle sodium ion battery according to claim 7, characterized in that: The cyclic ether includes at least one of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ether includes at least one of dimethoxymethane, 1,2-dimethoxyethane, and diethylene glycol dimethyl ether.
10. The high-safety long-cycle sodium ion battery according to claim 1, characterized in that: The electrolyte includes an electrolyte salt, and the electrolyte salt includes at least one of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium trifluoroacetate (CF3COONa), sodium tetraphenylborate (NaB(C6H5)4), sodium trifluoromethylsulfonate (NaSO3CF3), sodium bis(fluorosulfonyl)imide (Na[(FSO2)2N]) or sodium bis(trifluoromethylsulfonyl)imide (Na[(CF3SO2)2N]).
11. The high-safety long-cycle sodium ion battery according to claim 1, characterized in that: The electrolyte further includes an additive, wherein the additive includes a fluorinated carbonate.
12. The high-safety long-cycle sodium ion battery according to claim 11, characterized in that: The fluorocarbonate comprises at least one of fluoroethylene carbonate or difluoroethylene carbonate, and the mass percentage of the fluorocarbonate in the electrolyte is 1-5%.
13. The high-safety long-cycle sodium ion battery according to claim 1, characterized in that: The positive electrode comprises a positive electrode active material, and the positive electrode active material is selected from at least one of layered metal oxides, polyanion compounds, Prussian compounds, phosphate compounds, and sulfate compounds, wherein: The chemical formula of the layered metal oxide is Na x M y O z , 0<x≤1, 0<y≤1, 1<z≤2, M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V; The molecular formula of the Prussian compound is Na x M[M′(CN)6] y ·zH2O, M and M' are transition metals, 0 <x≤2,0<y≤1,0<z≤20; The chemical formula of the phosphate compound is Na3(MO 1-x PO4)2F 1+2x , 0≤x≤1, M is selected from at least one of Al, V, Ge, Fe, and Ga; or, the chemical formula of the phosphate compound is Na2MPO4F, and M is selected from at least one of Fe and Mn; The chemical formula of the sulfate compound is Na2M(SO4)2·2H2O, where M is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V.
14. The high-safety long-cycle sodium ion battery according to claim 13, characterized in that: The layered metal oxide is NaNi m Fe n Mn p O2 or NaNi m Co n Mn p At least one of O2, wherein NaNi m Fe n Mn p In O2, m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1; in NaNi m Co n Mn p In O2, m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1.
15. The high-safety long-cycle sodium ion battery according to claim 13, characterized in that: The Prussian compound is Na x Mn[Fe(CN)6] y ·zH2O or Na x Fe[Fe(CN)6] y At least one of zH2O, wherein Na x Mn[Fe(CN)6] y ·0<x≤2,0<y≤1,0<z≤20 in zH2O; Na x Fe[Fe(CN)6] y ·zH2O has 0<x≤2, 0<y≤1, 0<z≤20.
16. The high-safety long-cycle sodium ion battery according to claim 13, characterized in that: The phosphate compound is at least one of Na3(VPO4)2F3 or Na3(VOPO4)2F.
17. The high-safety long-cycle sodium ion battery according to claim 13, characterized in that: The phosphate compound is at least one of Na2FePO4F or Na2MnPO4F.
18. The high-safety long-cycle sodium ion battery according to claim 1, characterized in that: The negative electrode comprises a negative electrode active material and a conductive agent, wherein the negative electrode active material comprises at least one of hard carbon or soft carbon; and the particle size of the negative electrode active material satisfies 4 μm ≤ d 50 ≤8μm; in the negative electrode, the mass percentage of the conductive agent is 1%~5%.
Citation Information
Patent Citations
Coal-based soft carbon / hard carbon composite material as well as preparation method and application thereof
CN115133028A
Carbon nanosheet material, electrode plate and preparation method of electrode plate
CN115159504A